Attitudes and practices of young adults related to blood donation during the COVID-19 pandemic in Sri Lanka - Fazla, M.M.F.; Dileka, K.T.S.; Wickramasekara, K.M.H.M.; Oshana, B.V.; Piyumantha, B.V.D.; Wijekumar, P.J.; Nayanathara, R.K.A.B.; Ranadeva, N.D.K. (University of Jaffna, 2022)
Blood donation can save a million lives. A reduction in the numbers of potential donors was observed during the COVID 19 pandemic in Sri Lanka, where the need for an accelerated process of blood collection has been a concern of the health sector. This study aimed to determine the attitudes and practices of young adults related to blood donation during the COVID-19 pandemic in Sri Lanka. A cross-sectional study was conducted with 388 young adults in Sri Lanka, using a convenient sampling technique and an online structured self-administered questionnaire. There were three sections in the questionnaire: socio-demographic (Q-05), attitude (Q-05), and practice (Q-06). Data were analysed using IBM SPSS version 28.0. Among the total participants, there were 274 (71%) females and 114 (29%) males. Of 388 young adults, 26.5% (n=103) were previous donors and 73.45% (n=285) were non-donors. 33.5% of the study participants (n=130) claimed that it is safe to donate blood during the COVID-19 pandemic while the rest 66.5% (n=258) claimed it’s not safe. Out of the donor population (n=103), 44.7% (n=46) donated blood during the COVID-19 pandemic where it was noted that more than half of regular donors 55.3% (n=57) refrained from donating blood during COVID 19 pandemic. Further, no statistically significant associations were found between the positive attitudes of donors and blood donation during the pandemic situation. (p= 0.114). There was a statistically significant (p=0.003) association observed between donors and non-donors with their preference for donating blood during the pandemic in a safe environment. Also, 10.86 % of donors got the COVID-19 infection after visiting a donation camp. This study concluded that there was an overall negative attitude toward blood donation during COVID-19 and also observed a reduction in the regular practice of blood donation.
Keywords: Blood Donation; COVID-19; Attitude; Practices; Young adults